Frações de carbono e nitrogênio mineralizável no solo em sistema de integração lavoura-pecuária - Laurito, Henrique Fontellas [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
In research on soil management, organic matter is often fractionated, with emphasis on the labile fraction, which is the most sensitive to changes in management and the most directly associated with nutrient cycling. This sensitivity allows to save time to recommend the best strategies or propose adjustments in management to increase soil quality and sustainability of production systems. The objective of this study was to evaluate the physical fractions of carbon (Coarse and Fine Particulate Organic Carbon and Organic Carbon Associated with Minerals) and mineralizable organic N in an Integrated Crop-Livestock System (ICLS) in which different corn and marandu grass sowing systems were evaluated in the integration. The experiment was installed in 2015 at the Research Center for Beef Cattle of Sertãozinho, belonging to the Institute of Animal Science/APTA/SAA. The design of the experiment was randomized blocks with six treatments and three replications. The treatments were: Tillage (corn for grains); Livestock (marandu grass); ICLS1: corn plus marandu grass with simultaneous sowing in planting fertilization; ICLS2: corn plus marandu grass with simultaneous sowing in planting fertilization + application of nicosulfuron herbicide; ICLS3: corn plus marandu grass with marandu grass sowing in corn cover fertilization; ICLS4: corn plus marandu grass with simultaneous sowing of marandu grass in the corn line and between line + application of the herbicide nicosulfuron. The experiment was conducted until January 2018, when soil samples were collected at depths of 0-10 cm and 10-20 cm. Part of the collected soil volume was incubated for 28 days at 25°C (incubated samples) and the other part was kept at room temperature (non incubated samples) and, in incubated and non-incubated samples, carbon fractions and mineralized nitrogen were determined in 28 days of incubation. In the statistical analysis, monoculture corn and grass and sowing systems within the ICLS were considered the main treatments, and the depths, the secondary ones. The effects of treatments on POC levels before incubation and mineralized N were evaluated using variance analysis by f-test and comparison of means by Tukey test. Particulate organic carbon was higher in crop-livestock integration systems, particularly in ICLS1 (marandu-grass plus corn with simultaneous sowing in planting fertilization) and ICLS3 (marandu-grass corn with marandu grass sowing in corn cover fertilization). The sowing and management systems did not influence the mineralized nitrogen content. In the layer from 0 to 10 cm there was a higher content of mineralized nitrogen, particulate organic carbon and associated with minerals.

Em pesquisas sobre manejo de solo a matéria orgânica é frequentemente fracionada, com ênfase para a fração mais lábil, que é a mais sensível às alterações do manejo e a mais diretamente associada à ciclagem de nutrientes. Essa sensibilidade permite ganhar tempo para recomendar as melhores estratégias ou propor ajustes no manejo para aumentar a qualidade do solo e a sustentabilidade dos sistemas de produção. Com o presente trabalho objetivou-se avaliar as frações do carbono orgânico (C Orgânico Particulado Grosso, Fino e Associado a Minerais) e o N orgânico mineralizável em sistema de integração lavoura-pecuária (ILP) em que foram testados, na integração, diferentes sistemas de semeadura de milho de capim-marandu. O experimento foi instalado no ano de 2015, no Centro de Pesquisa de Bovinos de Corte de Sertãozinho, pertencente ao Instituto de Zootecnia/APTA/SAA. O delineamento do experimento foi em blocos casualizados com seis tratamentos e três repetições. Os tratamentos foram: Lavoura (milho para grãos); Pecuária (capim-marandu); ILP1: milho mais capim-marandu com semeadura simultânea na adubação de plantio; ILP2: milho mais capim-marandu com semeadura simultânea na adubação de plantio + aplicação de herbicida nicosulfuron; ILP3: milho mais capim-marandu com semeadura do capim-marandu na adubação de cobertura do milho; ILP4: milho mais capim-marandu com semeadura simultânea do capim-marandu na linha e na entrelinha do milho + aplicação do herbicida nicosulfuron. O experimento foi conduzido até janeiro de 2018, totalizando 2 ciclos de colheita do milho, quando foi feita coleta de amostras de solo nas profundidades de 0-10 cm e 10-20 cm. Parte do volume de solo coletado foi incubado por 28 dias a 25°C (amostras incubadas) e a outra parte foi mantida em temperatura ambiente (amostras não incubadas) e, nas amostras incubadas e não incubadas, foram determinadas as frações de carbono e o nitrogênio mineralizado em 28 dias. Nas mesmas amostras incubadas foi feita a determinação de N mineral para obtenção do N mineralizado em 28 dias. Na análise estatística as monoculturas de milho e capim e os sistemas de semeadura dentro do ILP foram considerados os tratamentos principais, e as profundidades, os secundários. Os efeitos dos tratamentos nos teores de COp antes da incubação e no N mineralizado foram avaliados empregando análise de variância pelo teste F e comparação de médias pelo teste de Tukey. O COp foi maior nos sistemas de integração lavoura-pecuária, particularmente na ILP1 (milho mais capim-marandu com semeadura simultânea na adubação de plantio) e ILP3 (milho mais capim-marandu com semeadura do capim-marandu na adubação de cobertura do milho). Os sistemas de semeadura e manejo não influenciaram no teor de nitrogênio mineralizado. Na profundidade de 0 a 10 cm houve maior teor de Nmin, COp e COam.
Carbon fractions and mineralizable nitrogen in the soil in an Integrated Crop-Livestock System
Keywords: Fertilidade do solo; Matéria orgânica no solo; Lavoura; Pecuária